PENGARUH PENGGUNAAN TEMPE SEBAGAI BAHAN DASAR PEMBUATAN ISIAN BURGER TERHADAP KOMPOSISI ZAT GIZI DAN DAYA TERIMANYA - nurwahyu utami; Jumirah .; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Tempeh burger is one of an innovative product of burgers, which has high phyto-protein. Most of people know that tempeh only made from soybean, but the other legume such as mung bean and red kidney bean can also be processed into tempeh because they almost have the similar nutrient composition with soybean. This was an experimental study that aims to determine the nutrient composition and the acceptable of patty with the difference of tempeh ingredients, such as soybean, mung bean, and red kidney bean. Based on laboratory test at the Laboratory of Nutrition FKM and Food Technology Laboratory FP USU, showed that the soybean tempeh patty has highest content of energy, fat, and carbohydrate; while the highest content of protein and ash belongs to the mung bean tempeh patty. Based on the organoleptic test by 30 students of FKM USU as a panelist, showed that the soybean tempeh patty was the most preferred. With Anova Test, the difference of tempeh for making the tempeh patty was only influenced different variety of color, aroma, and texture, but not for the taste. It’s recommended that consumer, especially those who like burgers but limiting meat consumption, make tempeh burger as their alternative snack. The mung bean tempeh patty was the best choice for young people who are still in their growth stage, because it had highest content of protein and ash. It is also need to do the further study to eliminate unpleasant contained in mung bean and red kidney bean tempeh patty. Keywords: Tempeh Patty, Nutrient Composition, Acceptability